Comparative evaluation of agglutination assay with microscopy and polymerase chain reaction for detection of Trypanosoma evansi in bovines of Punjab - SINGLA, L D; SHARMA, AMRITA; KAUR, PARAMJIT; BAL, M S (The Indian Journal of Animal Sciences, 2015)
Present investigation was aimed to evaluate the diagnostic efficacy of CATT/T.evansi in comparison to Giemsa stained thin blood smear examination and PCR for detection of bovine trypanosomosis in Punjab. Analysis of 264 blood and sera samples revealed 1.89% (5/264), 34.47% (91/264) and 51.89% (137/264) positivity by GSTBS, CATT/T. evansi and PCR, respectively, for Trypanosoma evansi. Sensitivity of CATT/T. evansi was 100% and 30.65% as compared to GSTBS and PCR, while its specificity was 66.79% and 61.42%, respectively. PCR is more sensitive and specific, and is able to detect the latent infections, however, it is time and cost ineffective technique. CATT/T. evansi is a quick and easy pen-site test suitable for mass screening of T. evansi endemic in developing countries.